1984
DOI: 10.1084/jem.159.1.221
|View full text |Cite
|
Sign up to set email alerts
|

Non-dinitrophenyl-binding immunoglobulin that bears a dominant idiotype (Id460) associated with antidinitrophenyl antibody is specific for an antigen on Pasteurella pneumotropica.

Abstract: We have previously described an idiotype (Id460) that transiently dominates anti-2,4-dinitrophenyl (DNP) antibody responses of mice that possess the appropriate Igh-V and V kappa genotypes. Normal serum has significant levels of Id460 that does not bind DNP, and hybridomas derived from spleen cell fusions that produce monoclonal antibodies with these characteristics have been generated. Many of these monoclonal, Id460-positive antibodies bind the opportunistic mouse pathogen Pasteurella pneumotropica. P. pneum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Antigeninduced anti-pneumococcal polysaccharide antibodies, for example, share idiotypic determinants with a large number of BALB/c myeioma proteins that bind phosphorylcholine (25). Similarly, antidinitrophenyl antibodies share idiotypic determinants with the myeloma protein MOPC 460 (27), and antibodies against a-l,3-a-l,6-dextran show idiotypes common to myeloma proteins J558, M 104, and U-102 (24,28).…”
Section: Gensmentioning
confidence: 99%
See 1 more Smart Citation
“…Antigeninduced anti-pneumococcal polysaccharide antibodies, for example, share idiotypic determinants with a large number of BALB/c myeioma proteins that bind phosphorylcholine (25). Similarly, antidinitrophenyl antibodies share idiotypic determinants with the myeloma protein MOPC 460 (27), and antibodies against a-l,3-a-l,6-dextran show idiotypes common to myeloma proteins J558, M 104, and U-102 (24,28).…”
Section: Gensmentioning
confidence: 99%
“…Another parallel between human and murine antibodies is the presence of the idiotype of an anti-DNA antibody in five antibodies that react with KlebsieUa antigens (NAE, WEA, ROS, MAY, and TO) (Table III). In the mouse, antiarsonate antibodies with the dominant arsonate-crossreactive idiotype-positive idiotype react with BruceUa abortus (cited in 12), and antibodies with the 460 idiotype (originally identified in antidinitrophenyl antibodies) react with Pasteu-reUa pneumotropica (27). The antibacterial properties of these antibodies, as well as those of the 16/6 family, may be a clue to their origin (29).…”
Section: Gensmentioning
confidence: 99%
“…Six were chosen for study: 2AB5 from the first spleen, Id16 from the second, and Id24, Id25, Id29, and Id30 from the third. Specificity for DNP or P. pneumotropica was tested as previously described (3,4).…”
Section: Methodsmentioning
confidence: 99%
“…
We have previously described an experimental system for studying the cellular and molecular basis of idiotype expression (1)(2)(3)(4)(5). BALB/c mice produce antidinitrophenyl (DNP) ~ antibody expressing a recurrent idiotypic determinant, Id-460.
…”
mentioning
confidence: 99%
“…Already in 1971 it was observed that idiotypic specificities could be expressed by immunoglobulins with different binding specificities ( 46 ). For instance, murine 2,4-dinitrophenyl (DNP) antibodies carry the Id460-idiotype which is also expressed on antibodies reacting with the mouse pathogen Pasteurella pneumotropica ( 47 ). A particular idiotope (B5 + ) of anti-dextran antibodies in BALB/c mice is expressed on a subset of antibodies from A/J mice that react with the hapten NIP ( 48 ).…”
Section: Principle Reactions In Idiotypic Regulationsmentioning
confidence: 99%